Early neutral evaluation in industrial court - Ali Mohamed, Ashgar Ali; Rosli, Muhammad Noor Firdaus (The Malaysian Current Law Journal Sdn Bhd, 2020)
This chapter discusses the early evaluation process with reference to the Industrial Court’s Practice Note No. 3 of 2010.